2018
DOI: 10.1177/0194599818776640
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy for Inverted Papilloma: A Proof‐of‐Concept Study

Abstract: Inverted papillomas are tumors of the sinonasal tract with a propensity to recur. Raman spectroscopy can potentially identify inverted papillomas from other tissue based on biochemical signatures. A pilot study comparing Raman spectroscopy to histopathology for 3 types of sinonasal tissue was performed. Spectral data of biopsies from patients with normal sinonasal mucosa, chronic rhinosinusitis, and inverted papillomas are compared to histopathology using principal component analysis and linear discriminant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other studies that address the clinical problem of incomplete resection of SNIP have also reported the use of alternative imaging techniques to discriminate between SNIP and uninvolved tissue [ 29 , 30 ]. Yet, these imaging methods are mainly limited to morphological information and therefore lack specificity to distinguish SNIP from surrounding inflammatory tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that address the clinical problem of incomplete resection of SNIP have also reported the use of alternative imaging techniques to discriminate between SNIP and uninvolved tissue [ 29 , 30 ]. Yet, these imaging methods are mainly limited to morphological information and therefore lack specificity to distinguish SNIP from surrounding inflammatory tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some of the tissue fragments contain normal tissue as well as SNIP or separately and not en bloc as seen in complete surgical resections. To better study the fluorescence signal within all tissue fragments, a grid of 25 × 25 pixels was used as an overlay for fluorescence images that have been obtained with the Odyssey CLX® flatbed scanner [ 30 ]. Each square was scored as either SNIP or uninvolved tissue based on the assessment of the pathologist (BvdV).…”
Section: Methodsmentioning
confidence: 99%